2013
DOI: 10.5194/acp-13-3587-2013
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of daytime HONO vertical gradients during SHARP 2009

Abstract: Nitrous acid (HONO) acts as a major precursor of the hydroxyl radical (OH) in the urban atmospheric boundary layer in the morning and throughout the day. Despite its importance, HONO formation mechanisms are not yet completely understood. It is generally accepted that conversion of NO2 on surfaces in the presence of water is responsible for the formation of HONO in the nocturnal boundary layer, although the type of surface on which the mechanism occurs is still under debate. Recent observations of h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
113
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(132 citation statements)
references
References 57 publications
18
113
1
Order By: Relevance
“…These HONO (g) formation mechanisms are consistent with field observations that suggest a relationship between the strength of the daytime HONO (g) source and the product of NO 2 and surface irradiance [Li et al, 2012;Ren et al, 2011;Wong et al, 2012]. These field observations also suggest that the NO 2 heterogeneous reactions described above can only account for a fraction of the required HONO (g) production [Sörgel et al, 2011b;Wong and Stutz, 2010;Wong et al, 2011;Wong et al, 2012].…”
supporting
confidence: 75%
See 2 more Smart Citations
“…These HONO (g) formation mechanisms are consistent with field observations that suggest a relationship between the strength of the daytime HONO (g) source and the product of NO 2 and surface irradiance [Li et al, 2012;Ren et al, 2011;Wong et al, 2012]. These field observations also suggest that the NO 2 heterogeneous reactions described above can only account for a fraction of the required HONO (g) production [Sörgel et al, 2011b;Wong and Stutz, 2010;Wong et al, 2011;Wong et al, 2012].…”
supporting
confidence: 75%
“…In fact, some points where the AIM-IC measures elevated mixing ratio equivalents of NO 2 À (p) are also periods where it measures more HONO (g) than the SC-AP instrument. This is expected if the ground surface is dominating conversion of NO 2 to HONO (g) at night, as vertical gradients have been observed to develop at the surface, and HONO (g) mixing ratios decrease with altitude VandenBoer et al, 2013;Villena et al, 2011;Vogel et al, 2003;Wong et al, 2011;Wong et al, 2012;Zhang et al, 2009]. To the extent that the AIM-IC and SC-AP were measuring air containing comparable levels of HONO (g) , Figure 1b further suggests that the PM 2.5 particle nitrite measurements from the AIM-IC are not the result of HONO (g) breakthrough from the gas channel.…”
Section: Intercomparison Of Hono (G) Measurements Between Aim-ic and mentioning
confidence: 99%
See 1 more Smart Citation
“…RCAT8.2 is a highly resolved one-dimensional chemistry and transport model that has been used to investigate the impact of nocturnal processes and daytime chemistry of HONO and NO 3 (e.g., Wong and Stutz, 2010;Wong et al, 2013;Tsai et al, 2014). It is based on the gas-phase Regional Atmospheric Chemistry Mechanism (RACM), which contains 77 species, 237 reactions, and aggregates atmospheric VOCs into 23 classes: four alkanes, four alkenes, three biogenic, three aromatics, and nine carbonyls (Stockwell et al, 1997).…”
Section: Rcatmentioning
confidence: 99%
“…Emissions of HONO from traffic were estimated by Kirchstetter et al (1996) and Kurtenbach et al (2001), who performed tunnel studies and reported exhaust emission ratio of HONO to NO x in a range of 0.003-0.008. The value of 0.008 is used in the Community Multiscale Air Quality (CMAQ) model to calculate HONO emissions from mobile sources (Foley et al, 2010) as well as in other models, for example, in a box model employed to study HONO sources in Houston (Wong et al, 2013). The relative contribution of HONO emissions from traffic to other sources when using the HONO to NO x ratio of 0.008 is about 9 % based on simulations for eastern US (Sarwar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%